Effects of Modafinil on Behavioral Learning and Hippocampal Synaptic Transmission in Rats - Wen-Wen Yan; Li-Hua Yao; Chong Chen; Hai-Xia Wang; Chu-Hua Li; Jun-Ni Huang; Peng Xiao; Cheng-Yi Liu (International Neurourology Journal, 2015)
Purpose: Modafinil is a wake-promoting agent that has been proposed to improve cognitive performance at the preclinical and clinical levels. Since there is insufficient evidence for modafinil to be regarded as a cognitive enhancer, the aim of this study was to investigate the effects of chronic modafinil administration on behavioral learning in healthy adult rats. Methods: Y-maze training was used to assess learning performance, and the whole-cell patch clamp technique was used to assess synaptic transmission in pyramidal neurons of the hippocampal CA1 region of rats. Results: Intraperitoneal administration of modafinil at 200 mg/kg or 300 mg/kg significantly improved learning performance. Furthermore, perfusion with 1mM modafinil enhanced the frequency and amplitude of spontaneous postsynaptic currents and spontaneous excitatory postsynaptic currents in CA1 pyramidal neurons in hippocampal slices. However, the frequency and amplitude of spontaneous inhibitory postsynaptic currents in CA1 pyramidal neurons were inhibited by treatment with 1mM modafinil. Conclusions: These results indicate that modafinil improves learning and memory in rats possibly by enhancing glutamatergic excitatory synaptic transmission and inhibiting GABAergic (gamma-aminobutyric acid-ergic) inhibitory synaptic transmission.